The Use of the Masquelet Technique in the Treatment of Pathological Distal Third Femoral Fracture Secondary to Chronic Osteomyelitis - Razvan Cosmin Tudor; Daniel Vasile Timofte; Norin Forna; Oana Viola Badulescu; Liliana Savin; Tudor Pinteala; Dan Mihailescu; Tudor Ciobotariu; Alin Ciobica; Mihnea Theodor Sirbu; Paul Dan Sirbu; Serban Dragosloveanu; et al. (Life)
Introduction: Chronic osteomyelitis is a persistent infection of the bone that poses significant challenges, particularly when associated with pathological fractures and extensive bone defects. This case report highlights the application of Masquelet’s induced membrane technique (MIMT) in managing a complex distal femur defect in a 50-year-old male with a long-standing history of chronic osteomyelitis. The patient presented with a non-union fracture, severe osseous destruction, and infection, requiring a multidisciplinary approach. Case report: The first stage involved radical debridement of necrotic tissue and stabilization with a titanium plate and an antibiotic-impregnated polymethylmethacrylate spacer to induce a bioactive membrane. The second stage, performed 30 days later, after infection resolution, entailed removing the spacer, harvesting an autologous iliac crest bone graft, and filling the defect within the preserved membrane. Postoperative care included a tailored antibiotic regimen and gradual weight-bearing, leading to favorable clinical and radiological outcomes. Conclusions: This case demonstrates the utility of MIMT in reconstructing extensive bone defects while addressing infection. The technique provides a reliable and effective alternative to amputation, offering high success rates and functional restoration in complex cases.